Transcriptome Analysis on Single Small Yellow Follicles Reveals That Wnt4 Is Involved in Chicken Follicle Selection - Wang, Yiya; Chen, Qiuyue; Liu, Zemin; Guo, Xiaoli; Du, Yanzhi; Yuan, Zhenjie; Guo, Miao; Kang, Li; Sun, Yi; Jiang, Yunliang (Frontiers in Endocrinology, 2017)
Ovarian follicle selection is an important process impacting the laying performance and fecundity of hens, and is regulated by follicle-stimulating hormone (FSH) through binding to its receptor (FSHR). In laying hens, the small yellow follicle (6–8 mm in diameter) with the highest expression of FSHR will be recruited into the preovulatory hierarchy during ovarian follicle development.The study of molecular mechanism of chicken follicle selection is helpful for the identification of genes underlying egg laying traits in chicken and other poultry species. Herein, the transcriptomes of chicken small yellow follicles differing in the mRNA expression of FSHR were compared, and a total of 17,993 genes were identified in three pairs of small yellow follicles. The Wnt4 signaling pathway was significantly enriched in the follicles with the greatest fold change in FSHR expression. In this pathway, the expression level of Wnt4 mRNA was significantly upregulated with a log2(fold change) of 2.12. We further investigated the expression, function, and regulation of Wnt4 during chicken follicle selection and found that Wnt4 mRNA reached its peak in small yellow follicles; Wnt4 stimulated the proliferation of follicular granulosa cells, increased the expression of StAR and CYP11A1 mRNA in prehierarchical and hierarchical follicles, increased the expression of FSHR mRNA, and decreased the expression of AMH and OCLN mRNA. Treatment with FSH significantly increased Wnt4 expression in granulosa cells. Moreover, Wnt4 facilitated the effects of FSH on the production of progesterone (P4) and the mRNA expression of steroidogenic enzyme genes in the granulosa cells of hierarchical follicles, but inhibited the effects of FSH in the granulosa cells of prehierarchical follicles. Collectively, these data suggest that Wnt4 plays an important role in chicken follicle selection by stimulating granulosa cell proliferation and steroidogenesis. This study provides a theoretical basis for improving the egg laying performance of chicken, and a reference for the elucidation of the molecular mechanism of follicular selection in mammals.